Application of Radiofrequency for Decolorization, Floc Formation, and Microorganism Inactivation - Javad Yahaghi; Alireza Bazargan (Tropical Aquatic and Soil Pollution, 2022)
The use of radio frequency for water and wastewater treatment is a topic that has not been extensively explored. In this study, the effect of a HydroFlow S38 device (Hydropath Holdigs) inducing 150 KHz radio frequency (RF) has been investigated, removing color, forming coagulant flocs and their sedimentation, and the removal of bacteria. Experiments were first conducted on synthetic samples, and then on landfill leachate from the Aradkooh waste processing and landfilling complex (Kahrizak) in Tehran, Iran. The results of the experiments showed that RF had little to no effect on de-coloring in the absence or presence of sodium hypochlorite. Also, the coagulation and flocculation of ferric chloride remained unaffected. However, the use of RF was shown to reduce the number of bacteria significantly. The inductance of RF alone, without any other aid or chemical/physical treatment, was able to reduce the bacterial count by 35%. These findings provide motivation for future research regarding the use of RF for bacteria inactivation.